Answer:
y = 1, x = 0
Step-by-step explanation:
multiply -4x +9y = 9 by -2 to get 8x -18y = -18
combine the two equations to get -8y = -8
divide both sides by -8 to get y = 1
plug in 1 as the y into one of the equations and solve to get x = 0
Answer:
(0,1)
x = 0
y = 1
Step-by-step explanation:
(-4x + 9y = 9)-8
(-8x + 10y = 10)4
32x - 72y = -72
-32x + 40y = 40
-32y = -32
y= -32/-32
y=1
-4x + 9(1) = 9
-4x + 9 = 9
-4x = -9 + 9
-4x = 0
x = 0/-4
x = 0
2x2(6x – 1) – 3(6x – 1)
6x(2x2 – 3) – 1(2x2 – 3)
6x(2x2 + 3) + 1(2x2 + 3)
The factorization of the given expression by grouping yields(6x-1)(2x²+3).
Factorization is a way in which the common factors of the terms in an algebraic expression are found. We have the expression 12x^3-2x²+18x-3 in which are to factorize by grouping.
In order to carry out this factorization by grouping we have to perform the following steps;
12x^3-2x²+18x-3
2x²(6x-1)+3(6x-1)
(6x-1)(2x²+3)
Learn more about factorization: brainly.com/question/6810544
B) −5x − 7 > −22 and −5x − 7 ≥ −3
C) −5x > −22 and −7 ≥ −3
D) −5x − 7 < −22 and −5x − 7 ≤ −3
The equivalent form of the compound inequality −22 > −5x − 7 ≥ −3 are A) −5x − 7 < −22 and −5x − 7 ≥ −3
If the equation or inequality contains variable terms, then there might be some values of those variables for which that equation or inequality might be true. Such values are called solution to that equation or inequality.
Then a Set of such values is called solution set to the considered equation or inequality.
The equivalent form of the given inequality can be obtained by dividing the inequality into two parts.
In this case, we are given -22 > -5x - 7 > -3.
The two parts are; -22 > -5x - 7 and -5x - 7 > -3.
Since the −5x − 7 and −22 have interchanged sides, the inequality sign also changes direction.
For part two, we have −5x − 7 ≥ −3 remains unchanged.
Therefore, The choice that reflects these parts is A)-5x - 7 < -22 and -5x - 7 -3
Hence, The equivalent form of the compound inequality −22 > −5x − 7 ≥ −3 are A) −5x − 7 < −22 and −5x − 7 ≥ −3
Learn more about inequalities here:
#SPJ2
Answer:
16
Step-by-step explanation:
3x^3-3x-2
x=2
3(2)^3-3(2)-2
3×8-6-2
24-6-2
16
Hope it helps.
Please mark brainliest